An exploration of violence, aggression, and abuse experienced by psychiatric nursing staff from patients at work - Patel, Davina (2019)
Chapter one gives some background information regarding the definitions of violence, aggression and abuse; the prevalence of these issues in psychiatric inpatient services, and sets up the aims of the thesis.